MODELING AND FORECASTING EXPORTS FROM BRAZIL MAKING USE OF TIME SERIES - TABLADA, Claudio Javier; RAMÍREZ, Fernando Arturo Peña; VIEIRA, Giannini Italino Alves; VASCONCELOS, Josimar M. de (Brazilian Journal of Biometrics, 2016)
Using available tools for time series and with the support of statistical software R, we intend to model and make predictions for h periods ahead (h = 1; 3; 6) under export data of Brazil from January 1995 to November 2012. For this end, dierent modeling techniques were used, as exponential smoothing algorithms and stochastic models. Initially, it was considered to be the Holt-Winters algorithm in its dierent versions and, additionally, models of type SARIMA and SARIMAX were selected. Finally, the power of forecast of the dierent models is analyzed using the relative errors of forecast as measure of evaluation.